Cognitive, educational, and behavioural outcomes at 7 to 8 years in a national very low birthweight cohort. Issue 1 (1st July 1998) - Horwood, L John; Mogridge, Nina; Darlow, Brian A
Abstract : AIMS: To examine cognitive, behavioural, and educational outcomes in middle childhood among a birth cohort of very low birthweight children. METHODS: Two hundred and ninety eight survivors from a national birth cohort of 413 New Zealand very low birthweight (VLBW) children born in 1986 were assessed at 7 to 8 years of age on measures of behaviour, cognitive ability, school performance and the need for special education. These outcomes were compared with the same measures in a general population sample of over 1000 children studied at a similar age. RESULTS: The VLBW children had significantly higher rates of problems and poorer levels of functioning across all outcome measures than the general child sample. These differences persisted even after control for variability in social, family, and other characteristics of the two samples and for the degree of sensorineural disability. There was evidence of a gradient of risk with birthweight, with extremely low birthweight children having generally higher rates of problems and difficulties than other VLBW children after covariate control. CONCLUSIONS: The findings are consistent with a growing body of research evidence which suggests that premature and VLBW infants are at increased risk of longer term morbidity and functional impairment in middle childhood.